Betalactamases: the evolution of the problem - Astocondor-Salazar, Lilian (2018)
The problem of antimicrobial resistance, is as old as the creation of the first antimicrobial, its irrational and indiscriminate use, has put in competition to the same bacterium who trying to survive generates mechanisms to evade these antimicrobials that the human being creates for the purpose with more spectrum, generating a vicious and endless cycle. Among its most successful mechanisms is the creation of enzymes called beta-lactamases which hydrolyze beta-lactams, the most widely used antimicrobial family in our times. Generating real public health problems in countries where their presence is evident above 50%, dramatically affecting morbidity, mortality and costs. From the foregoing, we believe it is necessary to understand the problem from the beginning, evaluating its evolution in different realities and the therapeutic alternatives we have in front of them.